Experimental Investigation of Efficiency and Deposit Process Temperature during Multi-Layer Friction Surfacing - Kallien, Zina; Roos, Arne; Klusemann, Benjamin (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2024)
Multi-layer friction surfacing (MLFS) follows the principle of the friction surfacing (FS) process, which is an established solid state coating technology for similar and dissimilar metallic materials. With this approach, the deposition of a consumable material on a substrate is enabled via friction and severe plastic deformation (SPD), processing the material below its melting temperature. The focus of the present study lies on the investigation of the temperature distribution during MLFS deposition. The measurements show that the temperature within the stack tends to be slightly higher on the advancing side. Additionally, the deposition behavior, i.e. deposition rate and consumable stud consumption rate, was investigated. Along MLFS stack height, deposition efficiency tends to sightly decrease, shown by decreasing layer thickness and increased length of remaining consumable studs. Overall, MLFS is highly repeatable for multiple layers and presents stable deposition conditions. Additionally, the technique has a comparatively low heat input to the substrate and the already deposited material.
Keywords: Additive Manufacturing; Dissimilar Aluminum Alloys; Multi-Layer Friction Surfacing; Solid State Layer Deposition; Temperature; 620 Ingenieurwissenschaften und zugeordnete Tätigkeiten